The Analysis of Causative Construction of Indonesia Republic President in Independence Speech - Nasution, Sarah; Mulyadi (TALENTA, 2024)
Speech is a medium for conveying formal messages through events/ceremonies. The state speech is part of the sacred event commemorating the Independence Day of the Republic of Indonesia. The state speech contains linguistic matters in it. Therefore, the author examines one form of linguistics, causative construction in the speech text. In this study, the authors limit the problem only to lexical and morphological causative constructions as a form of linguistic research. In speech texts, it was found that morphological causative constructions were dominant compared to lexical causative constructions. It is due to the morphological causative construction targeting the indirect cause, which is carried out by the subject so that the language conveyed becomes more meaningful in the speech.